Uwantme2killhim? [videorecording (DVD)] - Bachrach, Judy, 1948- (Tribeca Film, 2025)
An online relationship turns deadly in this true-crime thriller about a handsome 16-year-old boy who promises anything and everything to a girl he meets online. When a devastating crime is committed, the unbelievable truth is revealed.